In Silico and In Vivo: Evaluating the Therapeutic Potential of Kaempferol, Quercetin, and Catechin to Treat Chronic Epilepsy in a Rat Model - Ahmed, Hammad; Khan, Mahtab Ahmad; Ali Zaidi, Syed Awais; Muhammad, Sajjad (Frontiers in Bioengineering and Biotechnology, 2021)
Recently, alternative therapies are gaining popularity in the treatment of epilepsy. The present study aimed to find out antiepileptic potential of quercetin, catechin and kaempferol. In vivo and in silico experiments were conducted to investigate their therapeutics potential. The 25 mg/kg/day of pentylenetetrazole (PTZ was administered for four (4) weeks after the epilepsy was induced in the rats This is followed by the behavioural studies and histological analysis of rat brain slices. Binding affinities of Kaempferol, Quercetin and Catechin were assessed by performing in silico studies. Kaempferol, quercetin and catechin were found to have the highest binding affinity with the Synaptic vesicle 2A (SV2A) protein, comparable to the standard levetiracetam (LEV). The mRNA levels of SV2A, as well as the expression of TNF, IL 6, IL 1 beta, NFkB, IL 1Ra, IL 4, IL 10 were investigated using qPCR. Our results indicate for the first time that the that SV2A is also a transporter of understudied Phyto-flavonoids, due to which a significant improvement was observed in epileptic parameters. The mRNA levels of SV2A were found to be significantly elevated in the PF-treated rats when compared with the control rats with epilepsy. Additionally, down-regulation of the pro- and up-regulation of the anti-inflammatory cytokines was also noted in the PF-treated groups. It is concluded that kaempferol, quercetin and catechin can effectively decrease the epileptic seizures in our chronic epilepsy rat model to a level which is comparable to the anti-epileptic effects induced by levetiracetam drug.